WOMEN’S NGOs IN MONGOLIA AND THEIR ROLE IN DEMOCRATIZATION - TSETSEGJARGAL Tseden (Mongolian Journal of Anthropology, Archaeology and Ethnology, 2015)
The article reviews the development of Women’s NGOs in Mongolia and discusses the role of the Women’s NGOs in the process of a political transition to democracy. Women’s NGOs have a controlling weight in the civil society well beyond their formal percentage among other NGOs in Mongolia and have been at the forefront of democratic changes in Mongolia by pushing the government to increase its openness, transparency and accountability through their public education, policy advocacy and monitoring activities on a broad range of issues from women’s economic and political rights to violence against women including the domestic violence.